Surface anatomical landmarks for the location of posterior sacral foramina in sacral nerve stimulation - Povo, A.; Arantes, M.; Matzel, K. E.; Barbosa, Joselina; Ferreira, M. A.; Pais, D.; Rodriguez-Baeza, A. (Techniques in Coloproctology, 2016)
Sacral nerve stimulation is a common treatment for various pelvic floor disorders. It consists of the percutaneous introduction of electrodes through the posterior sacral foramina for therapeutic stimulation of the target sacral spinal nerve. The aim of our study was to determine the surface anatomical landmarks of the sacrum to facilitate identification of the posterior sacral foramina.This study was conducted on 20 human cadavers. The cadavers were placed in a prone position, and all the soft tissues of the sacral region were removed to allow exposure of the osseous structures. Different measurements were taken in relation to the posterior sacral foramina, the posterior superior iliac spine (PSIS) and the median sacral crest (MSC). A median coefficient of variation (CV) was determined.The diameter of the second sacral foramen showed the greatest variability. The distances between each individual foramen and the MSC had an acceptable variability (CV < 20%). In contrast, the distance between foramina had a high variability. The distance between PSIS and the second posterior sacral foramen was also found to have an acceptable variability (CV < 20%). However, the angle formed by an horizontal line between PSIS and a line between PSIS and S2 foramina had high variability.We found that the distance between sacral foramina and MSC is relatively constant while the distance between foramina and the relations between foramina and PSIS is highly variable. Detailed knowledge of the anatomy may facilitate electrode placement and is complementary to the regular use of fluoroscopy.
EVALuna2:15262